Development and clinimetric assessment of a performance-based functional vision tool in visually impaired children - Ghasemi Fard, Fatemeh; Mirzaei, Hooshang; Hosseini, Seyed Ali; Riazi, Abbas; Ebadi, Abbas; Hooshmandzadeh, Narges (Frontiers in Pediatrics, 2023)
Objective: Appropriate functional vision is vital for the development of visually impaired (VI) children. However, the literature currently lacks a performance-based tool for assessing functional vision, unlike the existing self-reported tools. The objective of this study is to develop and conduct a clinimetric study on a Performance-Based Functional Vision Tool (PB-FVT) specifically designed for VI children aged 3-7 and 7-10 years old. Methods: This methodological study was conducted to assess the clinimetric properties of the PB-FVT. The assessment included face validity (evaluated through cognitive interviews and an Impact Score > 1.5), content validity (with criteria including content validity ratio > 0.63, item content validity index > 0.78, scale content validity index or average > 0.8, and Kappa value > 0.7), criterion validity (assessed through a concurrent test using visual acuity scores), construct validity (utilizing the known group method), relative reliability (measured by the intra-class correlation coefficient), absolute reliability (determined by the standard error of measurement and minimal detectable changes), interpretability, responsiveness, sensitivity, and specificity (analyzed via ROC curve analysis). Results: The PB-FVT was developed with 32 items, divided into five components: activities of daily living, instrumental activities of daily living, education, play, and social interaction. The results indicate that the scale demonstrates suitability in terms of validity, reliability, and other measurement characteristics.The valid and reliable PB-FVT may accurately assess the level of functional vision during early childhood, helping to prevent negative impacts on a child's overall development. By utilizing the PB-FVT, any functional vision impairments can be identified appropriately, enabling the planning and implementation of effective rehabilitation interventions.